Impact of Timber Harvesting on Vegetation in the Ural Mountains - Ivanova, Natalya; Zolotova, Ekaterina (International Journal of Bio-resource and Stress Management, 2023)
Transformation of vegetation, which takes place in dark-coniferous forests under the action of clear timber harvesting in dominating forest habitats of the mountains of the Middle Urals, Russia, was studied. Harvesting was conducted 65 years ago. Research objects were 190-year-old spruce forests with domination in herbaceous layer of Oxalis acetosella L., 65-year-old birch forest with undergrowth of thick spruce, 65-year-old birch forest with undergrowth of sparse spruce and hay meadow. The plots were studied with regard to tree stand, understory and grass layer. Sample plots included no less than 200 woody plants. The undergrowth of trees on the tapes 20x4 m2 was studied. In order to determine the productivity of grass-dwarf shrub layer 10 to 20 record subplots of 1x1 m2 over period of maximum grass stand were established. The plants were cut at soil level, sorted by species, dried to an absolutely dry condition at the temperature of 105 °C and afterwards weighed. It was found that strong anthropogenic effects lead to appearance of a wide spectrum of vegetation communities within a single forest habitat (one type of indigenous forests). For a long time these vegetation communities differ by the structure of all vegetation layers, conditions of soil formation, and, consequently, by the direction and intensity of restoration processes. Age of spruce undergrowth was 65 years or more for most of the recorded trees. This undergrowth survived during harvesting. The reforestation direction was determined by the number of spruce undergrowth, which was stored in the timber harvesting.